Common auditors in mergers and acquisitions: Post‐acquisition financial reporting quality and audit fees - Ai, Xi; Myers, Linda A.; Schmardebeck, Roy (Contemporary Accounting Research, 2025)
Abstract Prior research documents that mergers and acquisitions result in significant financial reporting risks. In this article, we examine whether acquirers that share a common auditor with the target experience higher post‐acquisition financial reporting quality (FRQ) and reduced audit fees. We find that same‐office, but not different‐office, common auditors are associated with improved post‐acquisition FRQ, as evidenced by a decreased likelihood of misstatement, lower F ‐score, and a lower likelihood of meeting or just beating analyst forecasts. We also find that same‐office common auditors are associated with a lower percentage change in audit fees. In additional tests, we find that these inferences are robust to limiting the sample to acquirers with multiple acquisitions or to acquirers and targets with no auditor switches in the prior 3 years. Together, our findings suggest that same‐office common auditors facilitate knowledge transfer about the target and provide important post‐acquisition benefits.